Properties of cholesteryl oleate and triolein in mixed monolayers at the air-water interface. - J M Smaby; H L Brockman (Journal of Lipid Research, 1978)
The properties of cholesteryl oleate and triolein in mixed monolayers at the air-water interface have been measured between 24 and 37 degrees C. Analysis of force-area curves obtained as a function of the mol fraction of cholesteryl oleate indicates that at relatively low surface pressures these compounds are miscible in two dimensions up to a limit of about 0.5 mol fraction. At higher pressures either cholesteryl oleate or both lipids are expelled from the monolayer to form a bulk phase which is in rapid equilibrium with the surface phase. In the monolayer phase, orientation of the ester function of cholesteryl oleate is toward the aqueous phase, interaction with triolein is minimal, and packing is uniform over the solubility range. This together with the susceptibility of the cholesteryl oleate to enzymatic hydrolysis, suggests the applicability of monolayer systems to the study of cholesterol esterase activity. Comparison of our results with the bulk properties of these lipids suggests that the expelled cholesteryl oleate exists as a smectic mesophase and thus the system may provide a model for studying the transfer of molecules between the interior and surface of lipid deposits of the type found in atherosclerotic lesions.